Luxury tourism and sustainability: how are luxury consumers relating to sustainable tourism? - Spadoni, Francesca (2021)
This thesis presents a research on the relation between luxury consumers and sustainable tourism, and how they are approaching the topic. The issue of sustainability that is one of the most crucial problems faced by humanity, is managed by consumers in different ways. Overall, it is noticeable that consumers’ awareness of the topic is increasing steeply, and luxury industries are embracing green movements as a priority. However, sustainable tourism is still poised between convictions and paradoxes. The research outlines beliefs and concerns behind luxury clients’ perceptions about sustainable tourism, providing interesting hints for marketing operators and hospitality entrepreneurs.